1980
DOI: 10.1128/aac.17.5.901
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of moxalactam (LY127935) and cefotaxime against anaerobic bacteria

Abstract: The in vitro activities of moxalactam (LY127935 [6059S]) and cefotaxime were compared with those of cefoxitin, cefamandole, cefuroxime, carbenicillin, and penicillin by agar dilution susceptibility testing of a variety of anaerobic bacteria. Moxalactam proved to be the most active agent tested against Bacteroides fragilis and other species of the B. fragilis group. Moxalactam and cefotaxime showed activity similar to the other drugs against the remaining species of Bacteroides, Fusobacterium, Actinomyces, Prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
1

Year Published

1981
1981
1988
1988

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 7 publications
3
15
0
1
Order By: Relevance
“…Our results with moxalactam were similar to those reported by Jorgensen, Crawford andAlexander (1980) andBrown et al (1981) except that several strains of Bacteroides in our series had MICs > 64 pg/ml. Most strains of Fusobacteriurn spp.…”
Section: Discussionsupporting
confidence: 81%
“…Our results with moxalactam were similar to those reported by Jorgensen, Crawford andAlexander (1980) andBrown et al (1981) except that several strains of Bacteroides in our series had MICs > 64 pg/ml. Most strains of Fusobacteriurn spp.…”
Section: Discussionsupporting
confidence: 81%
“…Cefoperazone, cefotaxime, ceftizoxime, and ceftazidime are recently introduced cephalosporins which differ from their predecessors, such as cefoxitin, by alterations of the basic cephalosporin nucleus and its substituent groups. These new cephalosporins have been reported to have broader spectrum of activity than older agents and relative resistance to hydrolysis by beta-lactamases (10,16,20,26). In this investigation, cefoxitin, a beta-lactamase-resistant cephamycin, was level.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that many of the new antibiotics are effective against a wider range of bacteria than most of the currently used antibiotics suggests that one or more of these may be useful in a single-agent regimen. However, although many in vitro studies have shown that these antibiotics inhibit the aerobic organisms common to obstetric and gynecological infections (1,(12)(13)(14), there are few and only limited studies (6,7,9) of the effectiveness of these antibiotics against species of anaerobic bacteria, such as Bacteroides bivius and anaerobic gram-positive cocci, commonly isolated from pelvic infections (3,4 In an effort to expand on the above experience, we determined the minimal inhibitory concentrations (MICs) of cefoperazone, cefotaxime, cefoxitin, chloramphenicol, clindamycin, N-formimidoyl thienamycin, metronidazole, moxalactam, penicillin G, and piperacillin for 158 anaerobic bacteria isolated from endometrial wash cultures of 56 women admitted to San Francisco General Hospital with untreated pelvic infections (mostly salpingitis and endometritis). The organisms, identified through the use of gas-liquid chromatography and prereduced anaerobically sterilized media (5), were either recent isolates maintained in chopped meat broth or subcultures of isolates frozen in 10% skim milk at -70°C.…”
mentioning
confidence: 99%